2008
DOI: 10.1029/2007jd009332
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and acid‐mobilization study of iron‐containing mineral dust source materials

Abstract: Processes that solubilize iron in mineral dust aerosol may increase the amount of iron supplied to ocean surface waters, and thereby stimulate phytoplankton productivity. In particular, the uptake of acids such as H2SO4 and HNO3 on mineral dust surfaces can produce extremely acidic environments that promote iron dissolution. Here, four samples that represent source materials for mineral dust (Saudi Beach sand (SB), Inland Saudi sand (IS), Saharan Sand (SS) and China Loess (CL)) and one commercial reference mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
235
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(261 citation statements)
references
References 88 publications
(126 reference statements)
24
235
1
1
Order By: Relevance
“…α-FeOOH nanoparticles were synthesized according to the method of Anschutz and Penn (35) as previously described (11). Dropwise The spectra for adsorbed sulfate on nanorods and microrods are shown in B and C, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…α-FeOOH nanoparticles were synthesized according to the method of Anschutz and Penn (35) as previously described (11). Dropwise The spectra for adsorbed sulfate on nanorods and microrods are shown in B and C, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Journet et al showed that Fe-containing clays accounted for more than 90% of soluble iron (10). Cwiertny et al proposed that iron in the form of Fe 2þ in clay minerals is a highly labile source of iron (11). Other studies highlight the contribution from anthropogenic sources of soluble iron, mainly from combustion sources (3,12,13).…”
mentioning
confidence: 99%
“…Mezkhidze et al (2003) have assumed that hematite is an important source for the dissolved iron over the North Pacific, because most of the iron in surface soil of the Gobi deserts is found in the form of hematite (a-Fe 2 O 3 ) (Hseung and Jackson, 1952;Claquin et al, 1999). However, the assumption of hematite as the solely important source for dissolved iron may need to be revisited, as more comprehensive experimental data for chemical specificity of iron-rich dust become available (Cwiertny et al, 2008;Journet et al, 2008;Schroth et al, 2009;Fu et al, 2010). Here, the illite dissolution is also considered for specification of "structural iron", which is trapped in the crystal lattice of aluminosilicate minerals (RS4 in Table 1).…”
Section: Mineral Aerosol Dissolutionmentioning
confidence: 99%
“…Dust particles could become very acidic at the early stage of the transport before being neutralized by alkaline gases (Sullivan et al, 2007). Therefore, iron in aluminosilicate minerals potentially represents a significant source of soluble iron in the acidic environment (Cwiertny et al, 2008;Journet et al, 2008;Schroth et al, 2009). …”
Section: Model Sensitivity Studies and Analysismentioning
confidence: 99%
See 1 more Smart Citation